STRATEGI ADAPTIF GURU DALAM MENDAMPINGI SISWA TUNARUNGU DI SEKOLAH DASAR INKLUSIF - Rahmawati, Magdalena Chori; Supena, Asep; Bintoro, Totok (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2025)
This study aims to describe the strategies employed by teachers in supporting deaf students in inclusive primary schools. The background of the study is grounded in the principle of inclusive education, which guarantees the right of all children, including those with special needs, to receive equitable and quality education. A descriptive qualitative method was used, with data collected through observation, interviews, and document analysis. The research subjects included a classroom teacher, a school principal, and a deaf student at St. Fransiskus III Primary School in Jakarta. The findings revealed that the teacher’s strategies encompassed clear non-verbal communication, the use of visual media, repetition of information, and individualized approaches. The teacher managed the classroom by placing the deaf student in a strategic position and creating a supportive learning environment that encouraged social interaction. In terms of assignments and assessment, the teacher applied differentiation strategies by providing additional time and guidance. Moreover, the student’s progress was communicated directly to parents to foster close collaboration. The study also identified several challenges, such as limited time, lack of training, and constraints related to school policies and facilities. It concludes that the success of inclusive education is strongly influenced by adaptive teaching strategies and systemic support from the school environment and parents.